Exploring non-invasive approaches to assist in the detection of clandestine human burials: developing a way forward - Soren Blau; Jon Sterenberg; Patrick Weeden; Fernando Urzedo; Richard Wright; Chris Watson (Forensic Sciences Research, 2018)
The analyses of physical evidence recovered from clandestine single and mass graves have been demonstrated to be of significant evidential and/or investigative value for both court purposes and humanitarian investigations. The detection of these types of graves is, therefore, pivotal to forensic investigations. This article reviews different remote and ground-based methods that have been used to attempt to detect deliberately concealed burial sites and summarizes the experimental research that has, to date, been undertaken in order to improve grave detection. The article then presents the preliminary findings of research being undertaken at the Australian Facility for Taphonomic Experimental Research (AFTER). This research, the first of its kind to be undertaken in the southern hemisphere, is based on experimental single and mass graves using human cadavers. The research is centred on current remote sensing methods and techniques combined with the analysis of the effects of below-ground temperature and moisture and ground-based weather data. It is hoped that identifying successful sensors and detectors will be beneficial to national and international agencies that are involved in forensic as well as humanitarian investigations that require the detection of deliberately concealed gravesites.